Agricultural Financing - Agricultural Sector Output Nexus: A Case Study of The Nigerian Economy - Helen, Falaye Motunrayo (International Journal of Finance Research, 2023)
The study “Agricultural Financing -Agricultural sector output nexus: in Nigeria” investigated the effect of agricultural financing, both public and private on the outputs of two main sectors of agriculture: crop production and livestock production. Three objectives were formulated to provide guide to this study: examine the long and short run relationship of agricultural financing on crop production output and livestock production output, and to examine the causal relationship between agricultural financing and agricultural sector output.  To achieve these objectives, the study employed two models, each using ARDL Test, Bounds Test, and Granger causality test using time series data from 1981 to 2019.Data was obtained from CBN and World Bank data base. Dependent variables were Crop Production output and Livestock Production output respectively and independent variables were Public Finance, Commercial Bank Credit to Agriculture, Inflation Rate and Interest Rate. The model was tested using descriptive statistics to analyse the significance of the relationship between the dependent and independent variables.  The results show that both public and private finance were positive but insignificant in the short run. In the long run, public finance remained insignificant whereas private finance was positive and significant. Thus, private financing is more effective at improving agricultural output than public finance. The study also revealed a negative long run relationship between interest rate and the outputs of crop and livestock production during the period. It is therefore recommended that the government encourages private investment in agricultural activity, and puts measures in place to curb corruption and embezzlement. Government should also ensure that credit facilities are provided to farmers at low interest rate to reduce detrimental influences.